A defesa dos direitos humanos no Brasil, frente ao princípio do art. 4º, II, da Constituição Federal: a supremacia dos direitos humanos nos âmbitos interno e externo - Funari, Marcos Roberto (2019)
The safeguard of the human rights, for a dignified life, presupposes the guarantee of ideal conditions of freedom, equality and solidarity. In Brazil, as in other parts of the world, it is not uncommon to experience situations of disrespect for human rights that can be taxed if fundamental rights are not respected, with legislative backwardness or even with the lack of legislation guaranteeing them. In such cases, in order to prevent violations, to repair offenses and to improve guarantee mechanisms, the possibility of invoking the application of norms of international human rights law, in which the integrative principle of art. 4, II, in harmony with the rules of §§ 1 and 2 of art. 5 of the Federal Constitution of Brazil, plays a very important role. Such constitutional provisions concern the universalization and internationalization of human rights, but also lead to the interaction of national law with the international protection system. The opening made possible by the aforementioned constitutional dictates, besides providing greater effectiveness to fundamental rights, allows the control and monitoring of the international community, and even the supplementary action of international organizations for the protection of human rights, when national institutions do not act to the satisfaction, are not sufficient or do not exist. This is the only way to ensure the effective fulfillment of the Republic's objectives, to build a free, fair and supportive society, to assist in environmentally sustainable national development, to eradicate poverty and marginalization and to reduce social and regional inequalities, and to promote the all without prejudice of origin, race, sex, color, age and any other forms of discrimination. This work intends to explore the legal foundations that, under these circumstances, support the application of international human rights law in the Country